Johnson: The human touch. (Economist, 2021)
The article focuses on Grammar-checking computers' resistance to artificial intelligence illuminates the nature of language. Topics include Grammarly's training data involve a large number of standard error-free sentences, and software developers manually add certain rules to the patterns Grammarly has taught itself.